Pelatihan Pengemasan Tahu dan Sosialisasi Website Tahumurni.id Dukuh Taji Desa Gelanglor, Kecamatan Sukorejo, Ponorogo - Dyah Mustikasari; Jamilah Karaman; Riza Dessy Nila Ayutika (Pusat Riset dan Inovasi Nasional, 2025)
This community service program was designed to empower tofu micro, small, and medium enterprises (MSMEs) located in Dukuh Taji, Gelanglor Village, Sukorejo District, Ponorogo. The main focus of the program was to improve the quality and competitiveness of tofu products through training on modern packaging techniques and the introduction of digital marketing platforms. The implementation method combined training sessions and mentoring activities that provided participants with both theoretical knowledge and practical skills. In particular, the introduction of vacuum sealer technology allowed tofu MSMEs to produce packaging that is more hygienic, durable, and visually appealing, which significantly increased the added value of their products. In addition, participants were introduced to the use of the website tahumurni.id as a platform for online promotion and sales. Through guided practice, tofu producers successfully learned how to upload product information, manage online transactions, and engage with customers digitally. The outcomes of this program demonstrated that tofu MSMEs not only improved their product packaging but also expanded their marketing reach by entering online markets. This program made a significant contribution to strengthening the competitiveness of local tofu enterprises by integrating technological innovation with effective digital marketing strategies.